Pengembangan Materi Teks Fabel Berbantuan Media Capcut Video Editing Di Kelas VII SMP Negeri 6 Percut Sei Tuan - Evi Rizkita Dewi; Trisnawati Hutagalung (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This research aims to develop teaching materials for fable texts in the form of videos with the help of CapCut Video Editing media for class VII SMP. It is hoped that this teaching material will be able to help students carry out the teaching and learning process in class. This research is development research (RnD) which uses Borg and Gall research procedures. The product developed from this research is fable text teaching material in the form of video. The subjects of this development research include material expert validators, media expert validators, and students of class VII 1 of SMP Negeri 6 Percut Sei Tuan. Data collection techniques used include interviews with subject teachers and questionnaires that will be used to determine student needs and validate the feasibility of the product being developed. The research instruments used were student needs questionnaire sheets, material expert validation, media experts. The results of this research show that the product developed from this research, namely fable text teaching materials in the form of videos assisted by CapCut Video Editing media for class VII SMP, is already in very good qualifications with scores from material expert validators of 85%, media expert validators of 91.5% and The response from class VII 1 students was 87.9%, with an average score of 88%, so it can be concluded that the product in this research is very suitable for use by students in learning. .